Kyoto commitment and emission trading: A European Union perspective - Umberto Ciorba; Alessandro Lanza; Francesco Pauli (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper presents an estimation of the cost of reducing CO2 emissions as agreed in Kyoto by Annex I countries. Unlike most of the existing literature, this paper focuses on European Union countries' abatement costs and, using a simple model, estimates the role of each EU country within a EU market as well as an Annex 1 market. As a major result, marginal (and total) abatement costs for each EU country (as well as the EU total cost) are presented. Some conclusions on the redistribution of income among market participants related to the trading system are also shown.
Keywords: C13; C21; C53; Q38; Q41; Q48; 330; Environmental policy; Kyoto protocol; international agreements; CO2 emission; emission trading; marginal abatement cost; Umweltabkommen; Emissionshandel; Umweltkosten; EU-Staaten